La comunicación oral en inglés en estudiantes de segundo grado de secundaria en dos instituciones educativas de Maynas 2020 - Fonseca Pizango, Ursula Suja (2022)
The objective of this research study was to compare second year students’ oral communication in English at a private and a public secondary schools in Maynas province 2020. The type of research was comparative, with field study, contemporary transectional, and univariable designs. The population and sample consisted of 260 students, separated into two groups. 165 students from the public school and 95 from the private school. Results show that the oral communication mean score of the private school students is higher than the public school students (10,3 > 6,9), but both scores are in the beginner achievement category. The same applies to listening (15,6 > 10,7), as well as speaking (4,9 > 3,2). In conclusion, there is not statistically significant difference between the two groups’ oral communication in English as p- value was 0,000 < ? = 0, 05, accepting the working hypothesis.